2020
DOI: 10.1186/s40795-020-00334-x
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among Ethiopian adults living with HIV: a meta-analysis

Abstract: Background: Malnutrition and human immunodeficiency virus (HIV) are interlaced in a vicious cycle and worsened in low and middle-income countries. In Ethiopia, even though individuals are dually affected by both malnutrition and HIV, there is no a nationwide study showing the proportion of malnutrition among HIV-positive adults. Consequently, this review addressed the pooled burden of undernutrition among HIV-positive adults in Ethiopia. Methods: We searched for potentially relevant studies through manual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(39 reference statements)
3
13
0
Order By: Relevance
“…The magnitude of underweight in this study is consistent to the study from east Harerge zone (30%) (39), Ethiopia a systematic review and meta-analysis (27.4%) (40), Arba Minch town public health facilities (24%) (41), and Bench Shako zone (29.2%) (42).…”
Section: Discussionsupporting
confidence: 89%
“…The magnitude of underweight in this study is consistent to the study from east Harerge zone (30%) (39), Ethiopia a systematic review and meta-analysis (27.4%) (40), Arba Minch town public health facilities (24%) (41), and Bench Shako zone (29.2%) (42).…”
Section: Discussionsupporting
confidence: 89%
“…The problem is more prominent in Ethiopia as a result of food insecurity and inadequate knowledge about healthy nutrition [2]. Approximately 26% of adults living with HIV in Ethiopia are undernourished [3] as HIV increases nutritional requirements and reduces food intake because of mouth and throat sores, loss of appetite, medication side effects, and household food insecurity. Furthermore, it decreases nutrient absorption because of HIV infection of intestinal cells, diarrhoea, and vomiting [4].…”
Section: Undernutritionmentioning
confidence: 99%
“…Hepatocyte Nuclear Factor 4 alpha (HNF4α), or its variants, and the transcriptional factor Specificity Protein 1 (SP1) were inferred in different databases. Previous studies reported that the IL32 gene has a binding site for these transcriptional factors (39,40). However, we have inferred that the binding site overlaps with the rs45499297 polymorphism.…”
Section: Discussionmentioning
confidence: 55%
“…Malnutrition has been associated with HIV and HTLV1 (39,40), so it is inferred that genes co-expressed with IL32 are involved with these metabolic pathways, in addition to the fact that this cytokine is modified in malnourished states. This information is essential to understand disease mechanisms, especially in diseases with a high degree of complexity, such as obesity, in which several metabolic pathways are involved in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%